Intellectual Network of Mandailing and Haramayn Muslim Scholars in the Mid-19thÂ and Early 20th Century - Syahnan, Mhd.; Asrul, Asrul; Ja'far, Ja'far (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2019)
This paper is an attempt to study the scholars? network of Mandailing Ulama with those of Haramayn in the mid-19th  and early 20th century. Employing the content analysis method the research finds that the Mandailing scholars had made an intellectual encounter with the scholars in Haramayn, even some of the established networks with Egyptian and Indian scholars. The Mandailing scholars connote those who ethnically originated from Mandailing clan and data reveals that Mandailing scholars come from the residencies of Tapanuli and East Sumatera, both of which are parts of the modern era North Sumatera province. This not to deny that some of the Mandailing scholars were also born in Makkah. From the aspect of the duration of the study, some scholars studied religion intensively and settled in Makkah, while others only learned the Islamic religion by meeting the scholars of Makkah only during the Hajj period. The last group of scholars only studied religion intensely in Nusantara, but while performing hajj they met the scholars and learned religion in very limited time. Mandailing scholars studied Islamic sciences, especially Quranic exegeses, had?th, and Sufism to a number of such scholars from Arab and Nusantara as Ahmad Khatib al-Minangkabawi, ?Abd al-Qadir b. Shabir al-Mandili (Nasution) and Hasan Masysyath. Ideologically, they studied Islamic sciences in the context of the Sunn? school of thought, especially Ash?ar?yah and Sh?fi??yah. This study then fills the gap of the study of other researchers about the Nusantara Ulama Network with Middle Eastern scholars.